Bridging the gap between engineering design and marketing: insights for research and practice in product/service system design. (15th March 2018) - Brambila-Macias, Sergio A.; Sakao, Tomohiko; Kowalkowski, Christian
Abstract : Over the last decade, product/service systems (PSSs) have become a research issue in several disciplines, such as engineering design and marketing. The inherent interdisciplinary nature of this research issue has however remained unexploited. In order to bridge these silos and foster more interaction across relevant disciplines, this research examines PSSs from an interdisciplinary angle by analyzing how engineering design and marketing inform one another, as well as presents insights for PSS design. The research is carried out using a three-stage process for analyzing and evaluating interdisciplinary research: first, through a systematic literature review to identify relevant papers and their level of utilization across disciplines; second, by using a qualitative thematic analysis looking for different perspectives in order to find themes to bridge the gap between the disciplines; and third, by providing a research agenda to advance research by moving from silos to synergy. The results show a limited use of theories, frameworks, methods and tools across disciplines thus far, while the major contribution of this article lies in the implications derived for PSS design for academics and practitioners alike, which are categorized into seven specific themes: business orientation, collaboration, cost aspects, flexibility, performance indicators, requirements and services.